Exploring Seasonal and Annual Nitrogen Transfer and Ecological Response in River‐Coast Continuums Based on Spatially Explicit Models. Issue 1 (18th January 2022) - Chen, Nengwang; Wang, Jia; Liu, Xiaochen; Zhang, Caiyun; Huang, Bangqin; Beusen, Arthur H. W.; Middelburg, Jack J.; Bouwman, Alexander F.
Abstract: Perturbed nutrient balances in watersheds may eventually impact the marine ecosystem, but this river‐coast coupling is poorly understood. Monthly dissolved inorganic nitrogen (DIN) fluxes from seven major rivers in China were calculated by a global river nutrient model (IMAGE‐GNM), and then used in a regional ocean model system (ROMS) to explore changes in surface chlorophyll a (Chl a ) in the plume area (salinity <33) of the Taiwan Strait (TWS) in 2001–2010. Model results showed that river N input increased surface Chl a by a factor of 2.1–2.7, revealing a clear eutrophic response. Without river N input, there was only one Chl a peak in fall driven by current upwelling N. In contrast, sufficient river N supply and optimum temperature (above 20°C) likely caused another Chla peak (spring bloom) in the northern TWS (NTWS). The difference in the timing of spring blooms (Chla maxima) between the southern TWS (STWS) and the NTWS (April and May, respectively) may be explained by faster growth of phytoplankton at higher temperatures. Diagnostic analysis suggested that DIN was the main factor controlling interannual variation of Chla in the STWS, but only in the wet season in the NTWS. In the NTWS, reduced Chla in winter was mainly due to mixing by the strong northeast monsoon and lower temperatures. This study implies that the STWS is more sensitive to further increases in riverine N export and highlights the importance of fluvial N inputs in phytoplankton dynamics and the unique phenological features in the TWS. Plain Language Summary: The coastal zone is home to over 50% of the world's population and the location of almost 50% of global economic output. Human activities have substantially altered the nutrient balance in the watershed and coastal areas. Here, we show the ecological response of the Taiwan Strait (a unique ecosystem with strong coastal currents and a monsoon climate) to riverine nitrogen export using a global river nutrient model and an ocean model. Model results for the period 2001–2010 show that algal blooms (high Chla) occurred earlier in the southern Strait (April) than in the northern Strait (May). River N input has increased surface Chla in the river plume area (salinity <33) by a factor of 2.1–2.7 and caused another Chla peak (spring bloom) in the northern strait. Dissolved inorganic nitrogen was identified as the main factor controlling interannual variation of Chla in the southern strait, but in the wet season only in the northern strait. The southern strait is more sensitive to further increases in riverine N export due to higher temperatures. Key Points: Taiwan Strait annual variability in coastal Chla was mainly controlled by dissolved inorganic nitrogen River nitrogen input caused another Chla peak (spring bloom) in the northern Taiwan Strait Eutrophication in the southern Taiwan Strait is more sensitive to the increase of riverine nitrogen input